2011
DOI: 10.1002/lt.22370
|View full text |Cite
|
Sign up to set email alerts
|

Substance use by liver transplant candidates: An anonymous urinalysis study

Abstract: Toxicological urinalysis is a highly sensitive and specific test that detects recent substance use. It has been established for substance misuse treatment but has not been routinely used at liver transplantation (LT) centers. Patients with a history of substance misuse are required to be abstinent from alcohol and illicit drugs before they are listed for LT. In this cross-sectional study, we sought to determine the prevalence of recent substance use in LT candidates via toxicological urinalysis. One hundred ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 32 publications
0
38
0
4
Order By: Relevance
“…Among the reasons for monitoring and encouraging abstinence in ALD patients are the stabilization of their medical condition before surgery and the improvement of their prospects for long‐term sobriety afterward . Unfortunately, the recurrence of drinking is common even in ALD patients who have committed to abstinence and who have already been selected for liver transplantation . It has also been argued that with consistent abstinence, a candidate for ALD‐related transplantation might in fact no longer require a graft .…”
mentioning
confidence: 99%
“…Among the reasons for monitoring and encouraging abstinence in ALD patients are the stabilization of their medical condition before surgery and the improvement of their prospects for long‐term sobriety afterward . Unfortunately, the recurrence of drinking is common even in ALD patients who have committed to abstinence and who have already been selected for liver transplantation . It has also been argued that with consistent abstinence, a candidate for ALD‐related transplantation might in fact no longer require a graft .…”
mentioning
confidence: 99%
“…To date, most studies have focused on the use of UDS in screening patients for LT. 5 There are several limitations to our study including the fact that it is retrospective and from a single center, so the results may not reflect the practice or patient population at another center. As dis- In conclusion, we have shown PDMP to be a useful screening tool when used in conjunction with the UDS for detecting underreported CS use in LT candidates.…”
Section: Discussionmentioning
confidence: 98%
“…5 In recent years, statewide Prescription Drug Monitoring Programs (PDMP) have been employed to track the dispensing of CS so that providers can identify excessive use and abuse among patients. Webzell et al found that the prevalence of alcohol metabolites in patients with alcohol-related liver disease was 20%.…”
Section: Introductionmentioning
confidence: 99%
“…58 In a cross-sectional study of 109 adult patients undergoing assessment for liver transplantation, 20% of subjects with alcohol-related liver disease had positive urine EtG and EtS results, but only 4% self-reported alcohol use. 59 In a larger study of 141 liver transplant candidates in Germany, urinary EtG had a positive predictive value of 89.3% and a negative predictive value of 98.9% for detecting alcohol consumption and was superior to CDT, MCV and GGT. 60 Theoretically, end-stage liver disease could result in reduced production of EtG and EtS, although as these are minor pathways of alcohol metabolism, there is no evidence that such a reduction occurs.…”
Section: Applicationsmentioning
confidence: 92%